Predictors of outcome in guided self-help cognitive behavioural therapy for common mental disorders in primary care. Issue 6 (1st November 2020) - Salomonsson, Sigrid; Santoft, Fredrik; Lindsäter, Elin; Ejeby, Kersti; Ingvar, Martin; Öst, Lars-Göran; Lekander, Mats; Ljótsson, Brjánn; Hedman-Lagerlöf, Erik
ABSTRACT: Cognitive behavioural therapy (CBT) can effectively treat common mental disorders (CMDs), but access to treatment is insufficient. Guided self-help (GSH) CBT has shown effects comparable to face-to-face CBT and may be a resource-efficient treatment alternative. However, not all patients respond to GSH. Learning more about predictors of outcome may increase knowledge regarding which patients respond to GSH. The aim of this study was to investigate predictors of outcome for GSH CBT for patients with CMDs in primary care. Consecutive patients (N = 396) with a principal disorder of depression, anxiety, insomnia or stress-related disorders were included. All patients received GSH CBT. Outcomes were remission status, reliable change and post-treatment depression ratings. Predictors investigated were clinical, demographic and therapy-related variables. Analyses were conducted using logistic and linear regression. Higher educational level predicted remission, higher quality of life ratings predicted remission and decreased depression, and higher age at onset predicted reliable change. Therapy-related variables, i.e. patient adherence to treatment and patients' and clinicians' estimation of treatment response, were all related to outcome. More large-scale studies are needed, but the present study points at the importance of therapy-related variables such as monitoring and supporting treatment adherence for an increased chance of remission.